Pengembangan LKS Pintar Elektronik (Lekasparkin) Untuk Meningkatkan Minat Belajar Siswa SMA - Fatmala Nur Ardiani; Suharno Suharno; Akhmad Arif Musadad (Teknodika, 2017)
This study aims to (1) Explain the LKS used in learning in SMA 2 Bhineka Karya Boyolali, (2) describe the steps of developing the Electronic Smart LKS, (3) describe the results of the development of Electronic Smart LKS, and (4) test the effectiveness of Smart LKS Electronics produced. This type of research is research and development (R&D). The development research model used is the ADDIE model which consists of (1) Analysis, analyzing material and media materials needed in learning (2) Design, designing the draft of Electronic Smart LKS products in learning, (3) Development, Developing Electronic Smart LKS media in learning (4) Implementation of Electronic Smart LKS media and physical education materials (5) Evaluation. The subjects of this study were students of class XI SMA 2 Bhineka Karya Boyolali on physical education and sports subject material. Data collection techniques used were observation, interviews, documentation, and assessment sheets. The results of the assessment sheet assessment from media experts obtained an average of 85%, results from an average material expert 85.25%, one-on-one trial 85.75%, the results of small group trials phase I 77.88%, the test Phase II small group trials were 83% and field trials were 83%. The results of the experimental class obtained an average value of 82.88, while the control class obtained an average value of 68.00 verses or equivalent to 2.8 pages. Product effectiveness test results with a significance value of 5% obtained sig. (2-tailed) 0,000 <0.05. The conclusion of this study is that Electronic Worksheets can effectively increase student interest in learning